Application of Mobile-Based Games in The Rehabilitation of Stroke Survivors. (April 2023) - Norouzkhani, Narges; Hamednia, Mahsa; Aalaei, Shokoufeh
Background: Stroke, as a cerebral vascular accident, leads to brain injury which is characterized by interrupted blood flow. Indeed, impairments in the face, arms, and speech are usual symptoms of a stroke. A variety of disorders emerges after stroke, specificrehabilitation programs are used to restore the lost functions and improve the health status of the patient, mainly if they are applied early. In this study, we tried to present a comprehensive appraisal of recent findings and innovations in mobilegames intended for the rehabilitation of stroke survivors. Methods: Using keywords of interest including rehabilitation, stroke, mobile/computer, and application/game, a thorough search was performed in PubMed, Scopus, and Embase. Retrieved papers were scrutinized based on predefined inclusion and exclusion criteria. Results: Unfortunately, due to the limitations in the resources and facilities, early rehabilitation is not feasible in most cases. However, mobile technology is a promising avenue to address this hurdle, substantiating in the early rehabilitation practices in stroke patients.Mobile games hopefully brings a bunch of valuable outcomes and benefits, such as innovation, low-cost, and exciting approaches, both in clinical and home settings. Indeed, mobile devices save time, which could be spent to improve fine motor functions, leading to the acceleration of treatment for patients who are at home after discharge from hospitals. Conclusion: Acceptable motor improvement, visual perception, cognition, quality of life, satisfaction, and preferences of the patients are essential factors that should be considered in the design of theseapplications . It was shown that conventional strategies combined with such modern computer-based technologies might have synergistic effects on restoring the lost skills in stroke patients.